Being Invisible And a Minority: Adult Undergraduates in The University Classroom - Carol Kasworm Dr. (Adult Education Research Conference, 2006)
This study explored the social constructed understandings and meanings of student identity for undergraduate adults situated in research universities. Key findings suggested negotiated beliefs and actions within positional and a relational frames of being a minority in number and invisible in a culture focused on young adults.
Keywords: Adult undergraduates; adult student identity; adult learning engagement